The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Femmes et handicap - Masson, Dominique (Recherches féministes, 2013)
Les femmes handicapées, leurs réalités et leurs combats sont encore largement absents du courant de pensée majoritaire (mainstream) en études féministes qui, malgré un virage récent vers les analyses intersectionnelles, demeurent peu au fait des modalités d'analyse du handicap et des oppressions fondées sur les (in)capacités. Cet article veut permettre à un lectorat francophone de se familiariser avec les principales bases conceptuelles utilisées pour théoriser le handicap et les (in)capacités développées dans le domaine des études critiques du handicap, et en particulier par les auteures féministes travaillant dans ce champ. Il vise également à contribuer aux connaissances féministes des enjeux de transformation sociopolitique qui sont centraux pour les femmes handicapées, tels que ceux-ci sont révélés par les luttes de l'organisation féministe Action des femmes handicapées (Montréal). En conclusion, l'auteure explique la raison pour laquelle le handicap doit être considéré comme un enjeu féministe
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; canada; capacitisme; care; corps; cours; discipline; histoire et politique; intersectionnalité; justice sociale; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sciences humaines; sciences sociales; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études féministes

Par les mains pour les yeux : les représentations de l'identité sourde au sein de performances artistiques de la scène montréalaise - Paradis-Vigneault, Marie-Claude (Université Laval, 2012)
Ce mémoire s’appuie sur une recherche ethnographique réalisée principalement au sein de la communauté sourde de Montréal et tente de déceler les représentations de l’identité sourde au sein de performances artistiques de la scène montréalaise. Le but de cette recherche est d’inscrire la culture sourde dans les réflexions sociales et scientifiques portant sur l’expression identitaire de minorités culturelles par les arts. Afin de démontrer les liens à la fois théoriques et pratiques entre l’identité sourde et celles de minorités socio- politiques, telles que les Noirs, les gays, les femmes ou les Queers, cette étude s’appuie sur les concepts de performativité (Judith Butler), de performance (Clifford Geertz et Victor Turner) et de représentations (Stuart Hall et Serge Moscovici). Y seront également démontrées les relations entre ces notions, le vécu des sujets, leur agency et leur expression artistique.
http://hdl.handle.net/20.500.11794/23701
Keywords: amériques; anthropologie; approches et analyses; capacitisme; danse; discipline; histoire et politique; montréal; mémoires/thèses; performativité; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; théâtre; étude qualitative

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap